Literary Calendar, Oct 2022-June 2023 - Sy, Jose Monfred C. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 17 No 1 (2023): LIKHAAN 17: The Journal of Contemporary Philippine Literature, 2023)
October 2022-June 2023